Pelatihan Belanja Online dan Jasa Antar Langsung Pada Pedagang Pasar Tradisional di Pasar Wadung Asri Sidoarjo - Ella Anastasya Sinambela; Rahayu Mardikaningsih (Forum Kerjasama Pendidikan Tinggi, 2022)
Community service activities are carried out as a form of concern for others. Community service is carried out as a forum to provide assistance in the form of knowledge to the community. This activity indicates that the implementers of community service activities contribute to the progress of the nation. This community service activity was carried out by a lecturer at Sunan Giri University, Surabaya. This training was attended by 20 vegetable traders in Sidoarjo's Wadnung Asri Market. This activity is carried out to help traditional traders at the Wadung Asri Market, Sidoarjo. The implementation of community service activities is carried out for approximately 2 hours. The presentation and training was carried out so that traditional traders at the Wadung Asri market in Sidoarjo could provide delivery services to customers and shop online with the Whatsaap application. This is done so that traditional traders can keep up with technological developments that have been applied to the modern market. In this activity, materials such as plastic and rope are also provided to make safe packaging when providing direct delivery services to customers. In addition, this activity is also carried out to build good relations between the community and the community of Sunan Giri University Surabaya